2008
DOI: 10.1074/jbc.c800113200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Escherichia coli Polynucleotide Phosphorylase by ATP

Abstract: Polynucleotide phosphorylase (PNPase), an enzyme conserved in bacteria and eukaryotic organelles, processively catalyzes the phosphorolysis of RNA, releasing nucleotide diphosphates, and the reverse polymerization reaction. In Escherichia coli, both reactions are implicated in RNA decay, as addition of either poly(A) or heteropolymeric tails targets RNA to degradation. PNPase may also be associated with the RNA degradosome, a heteromultimeric protein machine that can degrade highly structured RNA. Here, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 47 publications
3
28
0
Order By: Relevance
“…This results in PNPase activation, while highly aerobic conditions inhibit PNPase (90). Cyclic di-GMP joins a growing group of small molecules that allosterically regulate PNPase activity and RNA turnover (358,359).…”
Section: Cyclic Di-gmp and Rnamentioning
confidence: 99%
“…This results in PNPase activation, while highly aerobic conditions inhibit PNPase (90). Cyclic di-GMP joins a growing group of small molecules that allosterically regulate PNPase activity and RNA turnover (358,359).…”
Section: Cyclic Di-gmp and Rnamentioning
confidence: 99%
“…Hfq was also shown to interact with the polynucleotide phosphorylase (PNPase) (Mohanty et al 2004), a major 39-59 exonuclease involved in RNA degradation (Andrade et al 2009b). PNPase responds to environmental stimuli, and its activity is modulated by metabolites such as ATP, citrate, and cyclic di-GMP (Del Favero et al 2008;Nurmohamed et al 2011;Tuckerman et al 2011). We have previously shown that PNPase is a key factor in the turnover of small RNAs controlling the expression of outer membrane proteins in the stationary phase of growth (Andrade and Arraiano 2008).…”
Section: Introductionmentioning
confidence: 99%
“…86 The role of CsdA in mRNA degradation was suggested by the observations that it (1) is found in degradosomes in cold-adapted 5'-diphosphate from the 3' end of the substrate and also carries out the reverse reaction of nucleoside 5'-diphosphate polymerization with the release of phosphate; 120 both the phosphorolytic and polymerization activities are allosterically inhibited by ATP. 121 The polymerization activity of PNPase is responsible for residual RNA tailing observed in E. coli mutants devoid of the main polyadenylating enzyme PAP I. 122,123 PNPase-dependent RNA tailing and degradation occur mainly at low ATP concentrations, whereas other enzymes may play a more significant role at high energy charge.…”
mentioning
confidence: 99%